2009
DOI: 10.1159/000264670
|View full text |Cite
|
Sign up to set email alerts
|

Adult Xanthogranuloma Mimicking Basal Cell Carcinoma: Dermoscopy, Reflectance Confocal Microscopy and Pathological Correlation

Abstract: Juvenile xanthogranuloma in adulthood is an infrequent non-Langerhans cell histiocytosis, which may simulate malignant tumors such as basal cell carcinoma (BCC) or amelanotic melanoma. Dermoscopy has been described as a useful tool in the preoperative diagnosis of xanthogranuloma. We report a xanthogranuloma on the suprapubic area of a 48-year-old female, which clinically and dermoscopically mimicked a BCC with a yellowish hue and arborizing vessels. Reflectance confocal microscopy exhibited large highly refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
(23 reference statements)
1
19
0
5
Order By: Relevance
“…The remaining misdiagnosed lesions belonged to rare benign skin tumours (i.e. angiomyxoma, apocrine hydrocystoma, xanthogranuloma) for which RCM diagnostic findings have been discovered, with the exception of xanthogranuloma, and this can explain well the discordance with the histopathological diagnosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The remaining misdiagnosed lesions belonged to rare benign skin tumours (i.e. angiomyxoma, apocrine hydrocystoma, xanthogranuloma) for which RCM diagnostic findings have been discovered, with the exception of xanthogranuloma, and this can explain well the discordance with the histopathological diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…Thirty‐six RCM criteria according to distinct diagnosis are reported in Table along with the references where they were first described . RCM criteria for melanoma metastasis (in transit) have not been described and we used the same diagnostic criteria as for melanoma.…”
Section: Methodsmentioning
confidence: 99%
“…The most prevalent dermoscopic feature of juvenile xanthogranuloma (JXG) is the “setting sun appearance,” which is defined as orange–yellow background with a subtle erythematous border; however, JXG alters its features gradually in terms of clinical, histopathological, and dermoscopic appearance. Song et al .…”
mentioning
confidence: 99%
“…Thus, it was suggested that cases with deeper extension of tumor cells to the dermis more closely mimic pigmented basal cell carcinoma on dermoscopy. In any case, arborizing vessels were observed not only in basal cell carcinoma but also in various kinds of benign skin tumors such as xanthogranuloma [8], angiohistiocytoma, hidradenoma and intraepidermal poroma [9]. Another 3 cases showed the coexistence of comedo-like openings and hairpin vessels, although they were irregularly shaped, and therefore seborrheic keratosis was suspected.…”
Section: Discussionmentioning
confidence: 99%